Microwave synthesis of novel methacrylate monomers designed to reduce biofilm formation to surfaces - Dundas, Adam Alastair (2018)
Rational design of biomaterials is hindered by the lack of quantitative structure-activity relationships (QSAR). Here we report the use of a QSAR to guide experimentation into a new chemical space; we predict and synthesize molecular structures for novel monomers that will reduce biofilm formation, and so identifying the lowest biofilm attachment polymer discovered to date. Cyclododecyl methacrylate was shown to reduce the formation of P. aeruginosa and P. mirabilis biofilms by up to 96 % and 97 % respectively compared to commercially available catheters. We believe that this is the first instance of a biomaterials screening program extending beyond the domain covered by the initial screen to predict a novel chemical entity with improved properties. This validates the QSAR approach for identifying polymers that resist biofilm formation beyond its chemical training domain. High throughput discovery of the non-commercially available material space is hindered by the ability to synthesize large numbers of materials in a controlled reaction process to keep up with supply demands. In this thesis we also present the production of a microwave single-well reactor capable of synthesizing novel methacrylate monomers using a transesterification process, where the design of the reactor has shown to outperform both conventional and standard microwave heating techniques. Powers as low as 40 W have been used to achieve reaction temperatures of 160 ˚C, showing great scale-out potential. With the approach of using QSAR for identifying potential biomaterials, monomer libraries can be judiciously chosen and then synthesised to enable high throughput discovery programs to have unprecedented access to the non-commercially available space.